2011
DOI: 10.4061/2011/860518
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Follicular Dynamics during the Estrous Cycle in Jennies in Upper Egypt

Abstract: The objective of the current study was to describe follicular dynamics in Egyptian Jennies throughout the estrous cycle. In this experiment, 8 estrus cycles in 8 cyclic Jennies were studied from February to June using ultrasonography. The result revealed that one follicular wave per cycle was recorded throughout the studied period. Dominant follicle (DF) was firstly detected at −0.80 ± 0.84 day in Jennies. The growth rate of DF was 2.32 ± 0.18 mm/day. Left ovulations were nonsignificantly (P = .07) more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Meanwhile, the follicles appear to be black colour (anechoic) because it contained fluid. These findings were similar to that of the living animal, that is Egyptian Jennies (Derar & Hussein, 2011), ewes (Liu et al, 2006), bitches and queens (Davidson & Baker, 2009b).…”
Section: Discussionsupporting
confidence: 82%
“…Meanwhile, the follicles appear to be black colour (anechoic) because it contained fluid. These findings were similar to that of the living animal, that is Egyptian Jennies (Derar & Hussein, 2011), ewes (Liu et al, 2006), bitches and queens (Davidson & Baker, 2009b).…”
Section: Discussionsupporting
confidence: 82%
“…In most donkey breeds the dominant follicle grows 2-3 mm/day from deviation to ovulation 13,16 , however, in Catalonian donkeys, a large breed, the follicles grow up to ~4 mm/day from follicular deviation to the static follicular growth phase 25 . In jennies, one follicular wave was identified during the estrous cycle 26 , whereas there were no follicular waves detected in mules 15 . The ovulatory diameter varies from 30 to 48 mm (Table 2), with a positive association between body frame and follicular diameter 10,16,27,28 .…”
Section: Estrous Cyclementioning
confidence: 91%
“…When using 450 IU of hCG, the mean diameter of the pre-ovulatory follicle was 34.5 mm, which is within the predicted range for the species, which may vary between 34 and 45 mm, for either induced or natural ovulation. Derar and Hussein (2011) obtained a mean diameter of 36 mm when evaluating follicular dynamics of donkeys during the estrous cycle, with spontaneous ovulation. Carluccio et al (2007) previously obtained a mean diameter of the pre-ovulatory follicle of 38 mm by inducing ovulation of follicles with a diameter between 30 and 35 mm with 2,500 IU of hCG, which is a higher dose than that used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum CL diameter found in donkeys was 30.7 ± 5.1 mm on D4, which differs from the results reported by Conceição et al (2009) , who found a maximum diameter of 26.2 ± 4.4 mm on D5 for simple ovulations following the luteal development of donkeys. Derar and Hussein (2011) , when evaluating the estrous cycle of donkeys, reported a maximum CL diameter of 26.77 ± 1.28 mm on D13, with the CL regressing until D17. These results demonstrate the efficiency of the use of subdoses of hCG in the ovulation protocol applied at the Hou Hai acupoint in donkeys, as well as for promoting the adequate development of CL when compared to CL formed from spontaneous ovulations, and those formed from induced ovulations with a higher dose of IV hCG (1,500 IU).…”
Section: Discussionmentioning
confidence: 99%